Protecting Persons While Protecting the People Second Annual Workshop on Information Privacy and National Security, ISIPS 2008, New Brunswick, NJ, USA, May 12, 2008. Revised Selected Papers - Gal, Cecilia S.; Kantor, Paul B.; Lesk, Michael E. (Security and Cryptology, 2009)
The Second Annual Workshop on Privacy and Security, organized by the Center for Interdisciplinary Studies in Information Privacy and Security of the School of C- munication and Information at Rutgers University, was held on May 12, 2008 at the Hyatt Regency, New Brunswick, New Jersey, USA. A few of the papers in this volume were produced through a multi-step process. First, we recorded the talk given by each author at the workshop in May 2008. Next, we transcribed the recording. The authors then produced a draft of their paper from these transcriptions, refining each draft until the final version. Although the papers are not verbatim transcriptions of the talks given, some do retain the informal and conv- sational quality of the presentations. In one instance we have included some material from the question-and-answer period after the talk, since the material covered proved to be relevant and interesting. The majority of authors, however, preferred to include a more formal paper based on the material presented at the workshop.